An Analysis Of Teacher Questioning Strategies In Elt (English Language Teaching) At Seventh Grade Of SMP In Nita Sub District - Maria Timu; Antonius M. K. Naro; Rikardus Nasa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The purpose of this research is to find out the types of questions used by English teachers during teaching and learning process. This is a qualitative descriptive research carried out at seventh grade in SMPs in Nita Sub District. Data were collected through class observation and interviews with teachers. The data is analyzed based on Miles and Huberman which consists of 3 techniques in analyzing data namely data reduction, data display, conclusion drawing and verification. The results showed that English teachers at seventh grade of SMPs in Nita sub district used six types of questions namely; remembering question, understanding question, applying question, analysis question, evaluating question, creating question. The impact of applying various questioning strategy during learning process are students become more enthusiastic about the learning in which they actively ask the teacher back if the material they cannot fully understand.